Menjalin Kedekatan Melalui Aplikasi Tinder - Khoiriyah, Aqilatul Munawaroh; Harjun; Hayati, Afita Nur (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2024)
This research aims to analyze the role of the Tinder application in forming social closeness and intimacy among students, using the Social Information Processing (SIP) theoretical framework. The method used is literature study, which involves critical analysis of scientific articles, journals, and other relevant library sources. The research results show that Tinder users utilize app features such as profiles, bios, and messaging systems to build initial impressions, reduce uncertainty, and gradually reveal more personal and emotional information. This process is in line with SIP principles, where text-based communication can facilitate the formation of social closeness comparable to offline interactions, although it takes longer. Furthermore, it was found that relationships formed through Tinder follow development stages similar to offline relationships: orientation, affective exploration, affective exchange, and stability. This research confirms that Tinder, although limited to text-based communication, can facilitate the formation of meaningful social closeness and intimacy among students and expand the application of SIP theory in the context of modern communication technology.